Fast Growing Furious Races for Targeting Fibroblast Growth Factor Receptors - Park, Daechan (Molecules and Cells, 2022)
Targeting fibroblast growth factor receptors (FGFRs) has been slow compared to other targeted cancer therapies for receptor tyrosine kinases, such as epidermal growth factor receptors. The low efficacy and variable response have limited the growth of FGFR inhibitors in clinical use. Nevertheless, recent systematic and genomic approaches have identified the biological conditions for effectively targeting FGFRs and can accelerate the development of targeted drugs. Under clinical and preclinical trials, the inhibitors started fast growing furious races to target FGFRs. Finally, FGFRs will be more actionable and targetable with more precise and effective drugs at the end of the race, passing the finish line.
Keywords: ErbB Receptors; Fibroblast Growth Factors; Protein Kinase Inhibitors; Receptor Protein-Tyrosine Kinases; Receptors, Fibroblast Growth Factor; Signal Transduction